Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Produktivitas Kerja Karyawan di PT Sumber Alfaria Trijaya Tbk Cabang Jababeka II - Satim Hamid; Nuranggi Safitri; Khoirunnisa Khoirunnisa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The increasingly intense competition in the retail business requires companies to improve employee work productivity in order to achieve targets and maintain competitiveness. This study aims to examine the influence of work environment and work motivation on employee productivity at PT Sumber Alfaria Trijaya Tbk Jababeka II Branch, both partially and simultaneously. This research uses a quantitative approach with the entire population of employees at PT Sumber Alfaria Trijaya Tbk Jababeka II Branch, and a non-probability sampling technique with 60 respondents. Data were collected through questionnaires and analyzed using multiple linear regression methods. The results showed that the work environment positively and significantly affected employee productivity, with a significance value of 0.00 < 0.05 and a t-count of 2.102 > t-table 1.672. Work motivation also positively and significantly affected employee productivity, with a significance value of 0.00 < 0.05 and a t-count of 12.810 > t-table 1.672. Additionally, the simultaneous test results showed that both work environment and work motivation positively and significantly affected employee productivity, with an F-count value of 141.738 > F-table 3.16. These findings indicate that improving employee productivity can be achieved through creating a conducive work environment and enhancing appropriate work motivation.